At the crossroads of uncertainty: Venezuelan migration to Colombia (2019)
THE SHARED 2,219-KILOMETER BORDER between Colombia and Venezuela was once considered one of the most dynamic borders in Latin America, as thousands of people would cross back and forth daily. The nature of mobility between the two countries has changed dramatically over the past decade, and with it the social geography of both nations. Beginning in the 1950s, large waves of Colombians migrated to Venezuela, an oil rich neighbor, where many found work and economic opportunities in Venezuela's social welfare state that were not available at home. The Colombian armed conflict also pushed hundreds of thousands of people toward Colombia's northeastern border, leading many to cross and seek refuge there in the 1990s and 2000s. By 2011, Colombians made up the largest population of foreigners living in Venezuela, almost 700,000 in total (Mejía Ochoa, 2012).